Rekonstruksi Keseimbangan Tanggung Jawab Negara dan Notaris dalam Memperkuat Perlindungan Hukum serta Pelayanan Publik di Indonesia - Teuku Abdurahman; Elly Safiana; Teuku Aldi Aulia Rahman; Teuku Laksamana Andrian Rahman; Teuku Aristio Ramadhana Rahman; Jabbar AL Ghifari Khalil (Universitas Serambi Mekkah, 2026)
This study aims to analyze the reconstruction of the balance of responsibility between notaries and the state in strengthening legal protection and public services in Indonesia. The main issue is the imbalance of responsibility between notaries as public officials and the state as the authority giver, reflected in the neglect of notaries' rights, weak protection of notarial protocols, and the absence of pension guarantees. This research employs normative juridical, empirical, historical, and philosophical approaches, as well as a comparative method with the notary systems in the Netherlands and France. Data were collected through literature study and interviews with notaries and the Notary Supervisory Council in Aceh. The results show a disparity of responsibility, where the Notary Position Law only regulates authority and obligations without protecting notaries' rights, thus not reflecting the principles of balance. The state has mistakenly indoctrinated absolute independence which ignores its responsibility, while the Public Service Law is not consistently applied to notaries. Protection of notarial protocols as state archives is also weak without a centralized database system. This study recommends the reconstruction of notaries' rights in the Notary Position Law, the establishment of an independent Notary Institution, strengthening the Notary Supervisory Council, and an integrated electronic protocol storage system.